Potensi sektor ekonomi di kota samarinda - Soeharjoto Soekapdjo (INOVASI, 2019)
This study aims to determine the potential of  economic sector at Samarinda city. Data  used  form  2013-2017 GRDP  (constant prices at 2010), source from BPS.  Using  SLQ, DLQ analytical tools, Shift Share, and Klassen Typology. Results  of  this research  is  : progress in various sectors and  economic potential  shift   at  Samarinda  city  towards  service sector,  where  Samarinda has  slower  potential  development from  East Kalimantan province. All sectors have a strong  competitive potential,   prospective, and the sector is in the advanced but depressed category, and there are 3 sectors that are relatively left  behind.  Samarinda city  increasingly shows its identity as a metropolitan city.